1779. An Assessment of Antibiotic Treatment Guideline Adherence for Common Infections in a Tertiary Care Hospital with an Established Antimicrobial Stewardship Program in Kathmandu, Nepal. (15th December 2022) - Adhikari, Prabhat; Director, Medical; Bhumiratana, Adisak; Acharya, Subhash; Acharya, Upasana; Pant, Suman; Silwal, Sashi; Dawadi, Pratima; Koirala, Janak; Gyanwali, Pradip; Shrestha, Suman
Abstract: Background: Antibiotic treatment guidelines have been increasingly recognized as an effective tool to guide appropriate prescriptions and help curtail antibiotic resistance. We aimed to assess the quality of inpatient antibiotic prescribing practices for common infections in a tertiary centre in Kathmandu. Methods: We conducted a retrospective monocentric review of medical records of adult inpatients diagnosed with Urinary Tract Infection; Pneumonia; and Skin and soft tissue infection between January 2018 till December 2019. Adherence was defined as the prescription of antibiotics for mentioned infection fulfilling the correct choice, correct dose, and correct duration of therapy. Flow diagram 1 Medical Records Review to assess adherence to guideline Results: Clinical records of 354 inpatients were included in the analysis. Overall, 37.9% of antibiotic prescriptions were adherent to guideline recommendations. The non-adherent groups also had a higher proportion of patients in the age group between 45 and 60 years (66%, OR: 1.87, 95% CI: 1.09-3.21, p=0.2) and with the presence of co-morbidities (58%, OR: 0.44, 95% CI: 0.26-0.75, p< 0.1). The department categories, gender, number of comorbidities, infectious disease diagnosis, and history of antibiotic drug allergy had no significant effect reported on adherence. Incorrect selection (20%, or: 0.24, 95% CI: 0.07-0.79, p=0.19) and incorrect antibiotic dosage (21%, OR: 0.26, 95% CI: 0.08-0.82, p=0.02) were prescribed among patients diagnosed with urinary tract infection. Likewise, an incorrect dosage of antibiotics (40%, OR: 0.27, 95% CI: 0.07-0.97, p=0.05) was prescribed for patients with pneumonia. Pneumonia (52%) and urinary tract infection (32%, p< 0.01) had more de-escalations, while the antibiotic spectrum prescribed was significantly broad (81%, p< 0.001). Study Schema Conclusion: Our study revealed low adherence despite the availability of the updated guideline for an antibiotic prescription. These data demand an urgent need to confront the antibiotic prescription pattern in the tertiary care centres for tailored interventions to improve adherence to guidelines, particularly focusing on prescriptions of antibiotic types and in the elderly population. It is also an imperative to reduce the broad-spectrum antibiotic exposure to the patients with acute infections guided by the culture reports. Disclosures: All Authors : No reported disclosures.